Greek epigraphy and religion: papers in memory of Sara B. Aleshire from the Second North American Congress of Greek and Latin Epigraphy - Aleshire, Sara B.; Mackil, Emily Maureen; Papazarkadas, Nikolaos (Brill studies in Greek and Roman epigraphy, 2021)
Introduction / Emily Mackil and Nikolaos Papazarkadas -- No introduction needed : Sara Bavousett Aleshire / Ronald S. Stroud -- Greek religion and epigraphic corpora : what's Sacrae about Leges sacrae? / Laura Gawlinski -- Two studies on the epigraphy of Greek sacrificial butchery / Jan-Mathieu Carbon -- IG I3 250, the Eleusinian cults and Zeus Herkeios / Kazuhiro Takeuchi -- Notes on the decree on the sacred Orgas (IG II3 1.292) / Angelos P. Matthaiou -- On the conveyance of the sacred objects for the Eleusinian mysteries : an archaising Athenian assembly decree of the third century AD / Stephen Lambert -- An inventory list and a votive relief from the Sanctuary of Artemis Brauronia found in Oropos / Yannis Kalliontzis -- A prosopography of Athenian cult personnel during the Principate : preliminary considerations / Francesco Camia -- Victorious athletes of ancient Messene : old and new epigraphic evidence / Andronike Makres -- Divine utterances : answers on the new oracular tablets from Dodona / Elena Martín González -- Dedications from the dead? The strange case of Hermes Chthonios / Maria Mili and Jenny Wallensten -- Koan good judgemanship : working for the gods in IG XII.4.1 132 / Adele C. Scafuro -- The Chian sacred law of Parparia revisited / Georgia E. Malouchou -- The self-definition of Alexander the Great / F.S. Naiden -- Tantalus and hemorrhage : an inscribed Hematite gem and its tradition / Michael Zellmann-Rohrer.